2003
DOI: 10.1002/ijc.11680
|View full text |Cite
|
Sign up to set email alerts
|

Progression of chronic atrophic gastritis associated with Helicobacter pylori infection increases risk of gastric cancer

Abstract: We conducted a longitudinal cohort study to determine the association of Helicobacter pylori infection and the progression of chronic atrophic gastritis (CAG) with gastric cancer. A cohort of 4,655 healthy asymptomatic subjects was followed for a mean period of 7.7 years. H. pylori infection was established by serum specific antibodies and the presence of CAG was confirmed by serum pepsinogen. During the follow-up period, 45 gastric cancer cases were detected (incidence rate, 126/100,000 person-years). A univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
445
8
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 463 publications
(481 citation statements)
references
References 42 publications
18
445
8
10
Order By: Relevance
“…The study participants were mostly farmers, so a generalisation with respect to the entire Korean population cannot be assumed. The disappearance of incidence of childhood infection may have introduced temporality bias (Ohata et al, 2004). The history of gastric ulcer or gastritis did not affect the association of H. pylori infection to gastric cancer in our data (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…The study participants were mostly farmers, so a generalisation with respect to the entire Korean population cannot be assumed. The disappearance of incidence of childhood infection may have introduced temporality bias (Ohata et al, 2004). The history of gastric ulcer or gastritis did not affect the association of H. pylori infection to gastric cancer in our data (data not shown).…”
Section: Discussionmentioning
confidence: 54%
“…Several previous studies have demonstrated that the more advanced the stage of H. pylori-related CAG, the greater the cancer risk. 31,32,[40][41][42][43][44] Subjects with metaplastic gastritis, an end result of long-lasting H. pylori infection, are thus considered to be at particularly high risk of gastric cancer. Indeed, our previous longitudinal cohort study found that a group of middle-aged male subjects with metaplastic gastritis based on 2 serum tests-negative results for H. pylori antibody and positive results on the PG test-displayed an annual cancer incidence rate of about 0.87%, meaning that 1 cancer developed in 11.5 subjects during every 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our previous longitudinal cohort study found that a group of middle-aged male subjects with metaplastic gastritis based on 2 serum tests-negative results for H. pylori antibody and positive results on the PG test-displayed an annual cancer incidence rate of about 0.87%, meaning that 1 cancer developed in 11.5 subjects during every 10-year period. 31,32 Subjects selected for the present study were early cancer patients curatively treated with endoscopic resection and thus appear to constitute a subgroup at even higher risk for gastric cancer among subjects with metaplastic gastritis. A few previous studies have reported an annual incidence of metachronous cancer after endoscopic resection of about 1.3-4.0%, 45,46 while the annual cancer incidence rate in the present study was Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic atrophic gastritis (CAG) is an important precursor lesion in the development of intestinal type of gastric cancer [1]. Even though there is a worldwide decline in the incidence of this type of cancer, its public health burden is still high, with gastric cancer ranking fourth in cancer incidence and being the second most common cause of cancer-related deaths worldwide [2].…”
Section: Introductionmentioning
confidence: 99%